2000
DOI: 10.1007/s10434-000-0696-3
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma Protuberans of the Head and Neck

Abstract: Wide margin resection of head and neck DFSP predicts negative histological margins and impacts favorably on local recurrence-free survival. Frozen section analysis does not assess resection margins accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 27 publications
1
64
1
6
Order By: Relevance
“…11 The lesions can be multiple and may coalesce to form an indurated plaque (Fig 3), which on clinical examination is often violaceous. 12,13 The growth rate is variable; some lesions remain stable in size for many years, whereas others demonstrate slow progressive growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 The lesions can be multiple and may coalesce to form an indurated plaque (Fig 3), which on clinical examination is often violaceous. 12,13 The growth rate is variable; some lesions remain stable in size for many years, whereas others demonstrate slow progressive growth.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Treatment options include complete surgical excision, including wide excision and Mohs micrographic surgery, radiation, and imatinib mesylate. 2,11,31 Imatinib, a competitive tyrosine kinase inhibitor, is currently approved by the Food and Drug Administration for the treatment of adult patients with unresectable, recurrent, and/or metastatic DFSP, and this may in turn facilitate tumor resection and or decrease disfigurement. 32 After local resection, the 5-year survival rate is 93-100%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Late recurrences, more than 10 years post-excision, although rare, have been described. 15,18,29,31 Consequently, patients must be examined every three to six months during the first three years after surgery and annually for the rest of their lives.…”
Section: Prognosismentioning
confidence: 99%
“…1 Wide excision with histologically negative margins is the cornerstone of treatment, but relatively high recurrence rates are described in the literature, [1][2][3][4] especially for DFSP lesions located on the head and neck. 5,6 Despite the achievement of "negative" margins, it is believed that the high recurrence rate is due to the fact that large portions of the true margins are not evaluated by standard histologic processing, combined with the difficulty identifying the occult, fingerlike projections that are characteristic of DFSP and are responsible for tumor recurrence. An extensive review of the literature published in 1996 found a mean recurrence rate of 18% (range, 0 -60%) after treatment with wide local excision in 15 studies, with a total recurrence rate of 20% among all reviewed patients (100 recurrences of 489 reviewed patients).…”
mentioning
confidence: 99%